Implementasi Konsep Bauran Pemasaran (Marketing Mix) dalam Peningkatan Daya Saing Mitra PT. Yakult Indonesia Persada Mojokerto, Jawa Timur - Marsiska Ariesta Putri; Lativa Nurkhasana; Avitri Nova Ardiyanti; Andika Mustofa; Ikmal Aldino H (Fakultas Komputer dan Pendidikan Universitas Ngudi Waluyo, 2025)
This report presents an analysis of the Implementation of the Marketing Mix Concept in Enhancing the Competitiveness of PT. Yakult Indonesia Persada Partners. The methods applied in this study include direct observation, interviews with participants, and analysis of related documents. The results of the study indicate that the Implementation of the Marketing Mix Concept in Enhancing the Competitiveness of PT. Yakult Indonesia Persada Partners successfully improved students' understanding of the concepts taught, as well as providing new perspectives on the challenges faced in the field. In addition, students' active involvement in field activities helped develop their interpersonal and professional skills. The conclusion of this report emphasizes the significance of the Implementation of the Marketing Mix Concept in Enhancing the Competitiveness of PT. Yakult Indonesia Persada Partners as a bridge between theory and practice, and provides recommendations for improving collaboration between educational institutions and industry to maximize the benefits of this program for students. Kata Kunci: Strategi Pemasaran, Marketing MIX, Peningkatan Daya Saing